Belajar Islam dari Kontroversi: Analisis Pendidikan Agama Islam dalam Konten Debat Keagamaan di Media Sosial - Ari Yopi Ispa; Mona Novita; Jazilurrahman; Chusnul Muali; Nur Aisyah (PT Cendekia Education Center, 2026)
This study examines how controversial religious debate content on social media shapes Muslim audiences’ religious learning experiences and explores its implications for Islamic Religious Education in the digital era. While Islamic Religious Education has traditionally emphasized structured learning within formal institutions, contemporary religious knowledge is increasingly encountered through digital platforms characterized by controversy, rapid circulation, and public interaction. This study aims to analyze how Muslim audiences engage with controversial religious debate content, how religious learning emerges through such exposure, and what pedagogical implications arise for Islamic Religious Education. This research employed an exploratory qualitative approach combining digital observation, qualitative content analysis, and semi-structured interviews. Data were collected from 50 controversial religious debate contents circulated on social media between January 2023 and December 2025, approximately 450 purposively selected audience comments, and interviews with 20 active Muslim social media users. Data were analyzed thematically using NVivo 14. The findings show that controversial religious content can function as a trigger for informal religious learning through argument comparison, clarification seeking, further exploration, and personal reflection. However, this learning experience is pedagogically ambivalent, as it also involves emotional engagement, confirmation bias, symbolic competition, and simplified understanding of complex religious issues. The study concludes that Islamic Religious Education must expand beyond formal knowledge transmission by strengthening digital religious literacy, epistemic evaluation, and ethical engagement in navigating contested religious knowledge in digital environments.